2017
DOI: 10.1038/scsandc.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Altered spinal cord activity during sexual stimulation in women with SCI: a pilot fMRI study

Abstract: INTRODUCTION:The objective of this study was to assess the feasibility of the use of functional magnetic resonance imaging (fMRI) to evaluate the spinal activation during sexual response of the thoracic, lumbar and sacral spinal cord. MATERIALS AND METHODS: This is a laboratory-based pilot study in human females at a University-based medical center in the United States. In three healthy spinal cord injury (SCI) females, spinal cord activations during sexual audiovisual stimulation (alone), genital self-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…While SCI is the most widely-studied patient population when using spinal fMRI, this technology has also been used to identify differences in spinal cord activity in response to different stimuli in multiple sclerosis [ 64 ], to characterize spinal cord responses to heat pain in fibromyalgia [ 53 ], and to show resting-state spinal cord activity differences in patients with cervical spondylotic myelopathy compared to healthy controls [ 65 ]. A recent case study was also reported in which the investigators examined activity in response to painful stimuli in a patient with referred pain [ 66 ].…”
Section: Applications In Patient Populations—broadening Our Undersmentioning
confidence: 99%
See 2 more Smart Citations
“…While SCI is the most widely-studied patient population when using spinal fMRI, this technology has also been used to identify differences in spinal cord activity in response to different stimuli in multiple sclerosis [ 64 ], to characterize spinal cord responses to heat pain in fibromyalgia [ 53 ], and to show resting-state spinal cord activity differences in patients with cervical spondylotic myelopathy compared to healthy controls [ 65 ]. A recent case study was also reported in which the investigators examined activity in response to painful stimuli in a patient with referred pain [ 66 ].…”
Section: Applications In Patient Populations—broadening Our Undersmentioning
confidence: 99%
“…The two most commonly used methods, GE-EPI and HASTE, demonstrate two very different strategies to achieve this balance. Spinal fMRI with HASTE methods (or variations of single-shot fast spin-echo) have been reported with repetition times of between 4.8 s and 9 s, with values around 6–7 s being the most common [ 22 , 23 , 24 , 25 , 28 , 31 , 33 , 34 , 36 , 37 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 53 , 54 , 55 , 56 , 57 , 60 , 61 , 62 , 63 , 64 , 66 , 76 , 77 , 79 , 80 , 81 , 82 , 85 , 87 , 88 , 97 , 102 , 103 ]. In most cases, data are acquired in sagittal slices and cover a large volume of the spinal cord.…”
Section: Temporal Resolution—balancing Sensitivity and Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggested that the lumbar spinal cord is motionless and the noise fitting can be ignored (Figley, Yau, & Stroman, 2008). Others only considered the cardiac motion-related effects on the spinal cord and CSF (Alexander et al, 2017;Alexander et al, 2016;R. Bosma & Stroman, 2015;Kozyrev et al, 2012), and both these approaches may lead to biased information due to ignoring the respiration noise as one of the main sources of noise production.…”
Section: Introductionmentioning
confidence: 99%
“…Functional Magnetic Resonance Imaging (fMRI) methods have been used to study sensorimotor processing in the brain and the spinal cord. Nowadays, spinal cord fMRI studies have investigated spinal cord in several pathologic conditions such as spinal cord injury ( Alexander, Kozyrev, Figley & Richards, 2017 ; Cadotte et al, 2012 ; Chen, Mishra, Yang, Wang, & Gore, 2015 ; Chen, Kong, Wang, Xie, & Wu, 2007 ; Choe, 2017 ; Stroman et al, 2004 ; Stroman et al, 2016 ; Zhong et al, 2017 ), multiple sclerosis ( Agosta et al, 2009 ; Agosta, Valsasina, Caputo, Stroman, & Filippi, 2008 ; Agosta et al, 2008 ; Kearney, Miller, & Ciccarelli, 2015 ; Rocca et al, 2012 ; Valsasina et al, 2010 ; Valsasina et al, 2012 ), chronic and neuropathic pain ( Bosma et al, 2016 ; Leitch, Cahill, Ghazni, Figley, & Stroman, 2009 ), all of which need consistent and sensitive clinical results. However, there are numerous challenges for spinal cord fMRI which arises from the nature of spinal cord: bony structure of the vertebral canal; movement of the cord and adjacent tissues due to physiological processes such as swallowing, breathing, and so on; the CSF flux in the subarachnoid space circumambient the spinal cord; small cross-sectional dimensions of the spinal cord and; changing in the susceptibility of tissues due to breathing and bulk motion ( Brooks et al, 2008 ; Fratini, Moraschi, Maraviglia, & Giove, 2014 ; Stroman et al, 2014 ; Verma & Cohen-Adad, 2014 ).…”
Section: Introductionmentioning
confidence: 99%